Examination of ejaculate fructose levels on male infertility patients at various times and centrifugation using semiautomatic method - Hermansyah Hermansyah; Muhammad Fadhli Abdullah; Cennikon Pakpahan; Reny I’tishom; Supardi Supardi; Ilhamsyah Ilhamsyah (Archivio Italiano di Urologia e Andrologia, 2024)
Objective: Various factors, such as obstructive azoospermia, cause infertility in men. Biochemical examination of ejaculate, especially measurement of fructose, can be an additional investigation that can be used for this diagnosis in reproductive health. Examination of fructose is carried out after routine ejaculate analysis, resulting in prolonging the examination time so that it will affect the measurement of fructose level in the ejaculate and the accuracy of the diagnosis. This study aims to determine the best timing and procedure for measurement of fructose using a semiautomatic method. Methods: This research is an analytic observational study conducted at Dr. Soetomo General Hospital, Surabaya. A total of 13 ejaculate samples from infertile male patients who met the inclusion criteria were evaluated. Each ejaculate was divided into eight aliquots that were examined for fructose using a semiautomated method after different intervals of time and centrifugation modalities. Results: This study showed a significant difference in fructose levels when aliquots were centrifuged and examined immediately or after different interval of time (p = 0.036). In addition, aliquots left standing for more than 60 minutes (p = 0.012) and 120 minutes (p < 0.001) before centrifugation, showed significantly lower levels compared to aliquots that were centrifuged and then immediately examined. Conclusions: We suggest that measuring fructose immediately after centrifugation is more reliable than measuring fructose left standing before or after centrifugation. Leaving the ejaculate standing will reduce the fructose level so that it does not resemble its real level.